STUDY OF METHYLENE BLUE INTERACTION WITH SYNTHETIC POLYNUCLEOTIDE POLY(rA)-POLY(rU) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
A study of the interaction of methylene blue (MB) with poly(rA)-poly(rU) by the method of fluorescence spectroscopy has been carried out. The data obtained revealed that MB, being a DNA-specific ligand, can bind to double-stranded regions of RNA. In this regard, as in the case of DNA, semi-intercalation was the most preferable mechanism for the binding of this ligand to poly(rA)-poly(rU). On the other hand, non-linear curves of dependence of F0/F on concentration of polynucleotide might result from two binding modes, the second of which was probably of an electrostatic nature. Proceeding from the data obtained, the value of KSV was revealed to be almost an order of magnitude less than for DNA, which may indicate that RNA is a less preferable target for MB.
Keywords: synthetic polynucleоtide; methylene blue; binding; fluorescence spectra; fluorescence quenching